The Dynamics of Seizures After Microsurgical Treatment of Brain AVMs in Patients with Symptomatic Epilepsy: A Single-Center Experience over 10 Years - Yerbol Makhambetov; Aiman Maidan; Iroda Mammadinova; Karashash Menlibayeva; Baurzhan Kunakbayev; Serik Dyussembaev; Nurtay Nurakay; Nursultan Makhambetov; Aigul Almabayeva; Chingiz Nurimanov (Medicina)
Background and Objectives: Arteriovenous malformations (AVMs) are abnormal connections between arteries and veins, lacking a normal capillary network. Seizures are a common clinical manifestation in patients with brain AVMs, ranking as the second most frequent presentation. The objective of this study was to evaluate the dynamics of seizure activity in patients with brain AVMs following surgical treatment. Materials and Methods: This study included 27 patients with brain AVMs who underwent microsurgical AVM resection for symptomatic epilepsy. All surgical interventions were performed at JSC “National Centre for Neurosurgery” between 2008 and 2020. Results: Over an average follow-up period of 98.07 ± 45.6 months, 82 patients with brain AVMs underwent open microsurgical resection at the National Centre for Neurosurgery. Among them, 27 patients presented with seizures and had complete follow-up information, qualifying them for inclusion in this study. The participants had a mean age of 32.59 ± 9.06 years, with 13 of them being women. The Spetzler–Martin grading system was used to classify the AVMs: 6 patients had grade 1, 13 had grade 2, 7 had grade 3, and 1 had grade 4. More than half of the patients experienced generalized seizures. Microsurgical removal of the AVMs resulted in seizure remission for all patients. Only one patient experienced postoperative hemorrhage during the follow-up period. Additionally, one patient developed acute postoperative anemia, which resolved with a favorable outcome. Conclusions: Microsurgical resection of brain AVMs, when performed with careful patient selection, leads to a significant reduction in seizure activity. It is a safe and effective treatment option for symptomatic epilepsy associated with brain AVMs.